Building sustainable research and data tools and partnerships for a healthy city for all. (20th October 2021) - Marriott, P; Hart, M
Abstract:  : Vancouver is located in a temperate rain forest surrounded by mountains and water. Indigenous communities, including the Nations whose homelands the city occupies, have recognized that the abundance of this place can build healthy communities for many generations. But contemporary Vancouver is not a healthy city for all. Since 2014, Vancouver has adopted a Healthy City Strategy, a master social sustainability plan to address inequities in the social determinants of health at a population scale. This includes a number of population health targets and indicators. However, implementation has been slow, with substantive integration of health into policy not yet achieved. With support from the Partnership for Healthy Cities, we have translated the Healthy City Strategy's indicators into an online dashboard, including disaggregated local data. In addition to public accountability, this tool enables data to be a platform for aligning city policy, action and investment toward common health outcomes. In parallel, we are also piloting more community-generated approaches to health data and indicators, with a focus on co-creating health indicators with Indigenous communities. Preliminary results have shown improvement in collaboration across city departments, leading to increased focus on upstream, preventive work. The dashboard is enabling frameworks for funding and working with the social service sector toward common health goals. Engagement efforts have shown the continued importance of a holistic strategy for health that is co-created with community knowledge and priorities. These interventions must be sustained and integrated into ongoing work. The technical work of developing the dashboard contributes to city-wide efforts toward data monitoring and reporting. Data has shown to be an important tool for beginning conversations, but sharing data about health inequities experienced by communities must be matched with an ongoing commitment to engagement and co-creation. Key messages: Population health data can be leveraged through interactive tools to better integrate and align city policies, plans and investments to address the social determinants of health. Engaging and co-creating policy with communities supports upstream, preventive action on health inequities.